Melatonin Supplementation Decreases Hypertrophic Obesity and Inflammation Induced by High-Fat Diet in Mice - Farias, Talita da Silva Mendes de; Cruz, Maysa Mariana; Sa, Roberta Cavalcante da Cunha de; Severi, Ilenia; Perugini, Jessica; Senzacqua, Martina; Cerutti, Suzete Maria; Giordano, Antonio; Cinti, Saverio; Alonso-Vale, Maria Isabel Cardoso (Frontiers in Endocrinology, 2019)
Obesity results from critical periods of positive energy balance characterized by caloric intake greater than energy expenditure. This disbalance promotes adipose tissue dysfunction which is related to other comorbidities. Melatonin is a low-cost therapeutic agent and studies indicate that its use may improve obesity-related disorders. To evaluate if the melatonin is efficient in delaying or even blocking the damages caused by excessive ingestion of a high-fat diet (HFD) in mice, as well as improving the inflammatory profile triggered by obesity herein, male C57BL/6 mice of 8 weeks were induced to obesity by a HFD and treated for 10 weeks with melatonin. The results demonstrate that melatonin supplementation attenuated serum triglyceride levels and total and LDL cholesterol and prevented body mass gain through a decreased lipogenesis rate and increased lipolytic capacity in white adipocytes, with a concomitant increment in oxygen consumption and Pgc1a and Prdm16 expression. Altogether, these effects prevented adipocyte hypertrophy caused by HFD and reflected in decreased adiposity. Finally, melatonin supplementation reduced the crown-like-structure (CLS) formation, characteristic of the inflammatory process by macrophage infiltration into white adipose tissue of obese subjects, as well as decreased the gene expression of inflammation-related factors, such as leptin and MCP1. Thus the melatonin can be considered a potential therapeutic agent to attenuate the metabolic and inflammatory disorders triggered by obesity.